2018
DOI: 10.1182/bloodadvances.2018019976
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning intensity in secondary AML with prior myelodysplastic syndrome/myeloproliferative disorders: an EBMT ALWP study

Abstract: Key Points• Allogeneic HCT can result in long-term survival for patients with sAML and prior MDS/MPN.• Myeloablative conditioning regimens should be selected for sAML and patients with prior MDS/MPN whenever possible.Patients with secondary AML (sAML) with antecedent myelodysplastic syndrome (MDS) or myeloproliferative neoplasms (MPNs) tend to have high-risk disease based on the older age of patients, high-risk cytogenetics, and higher number of prior treatments. was given to 40% of patients, and 60% receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 31 publications
6
29
1
Order By: Relevance
“…Indeed, while it did not reach statistical significance perhaps because of an insufficient study power, the incidence of relapse in patients transplanted in CR1 was 11% higher in patients given RIC than in those given MAC (29% vs. 18% at 2 years). This is consistent with a prior study in patients with de novo AML demonstrating more relapses in patients given CBT following RIC than in those given MAC regimens [21], and with a recent study showing lower risk of relapse and better OS in sAML patients given MAC (versus RIC) conditioning before HLA-identical sibling or HLAmatched unrelated donor transplantation [34]. Besides increasing the antileukemic activity of the conditioning regimens, further approaches to prevent relapse after CBT might consist of posttransplant administration of disease-targeted medications [35][36][37].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, while it did not reach statistical significance perhaps because of an insufficient study power, the incidence of relapse in patients transplanted in CR1 was 11% higher in patients given RIC than in those given MAC (29% vs. 18% at 2 years). This is consistent with a prior study in patients with de novo AML demonstrating more relapses in patients given CBT following RIC than in those given MAC regimens [21], and with a recent study showing lower risk of relapse and better OS in sAML patients given MAC (versus RIC) conditioning before HLA-identical sibling or HLAmatched unrelated donor transplantation [34]. Besides increasing the antileukemic activity of the conditioning regimens, further approaches to prevent relapse after CBT might consist of posttransplant administration of disease-targeted medications [35][36][37].…”
Section: Discussionsupporting
confidence: 91%
“…Two-year incidences of relapse and of NRM were 29% (95% CI, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and 39% (95% CI, 31-48), respectively. The figures were 25% (95% CI, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and 35% (95% CI, 25-45), respectively, in patients in CR1, versus 36% (95% CI, 22-49, P = 0.06) and 49% (95% CI, 33-62, P = 0.03), respectively, in patients with active disease at transplantation ( Fig. 1).…”
Section: Relapse and Nonrelapse Mortalitymentioning
confidence: 99%
“…Furthermore, the results may contribute to the design of optimized transplant protocols. Previous studies have suggested comparable outcomes after RIC and MAC in sAML, however, with a trend for better outcome after MAC 11,29 . Hence, a myeloablative, but reduced toxicity conditioning regimen such as the combination of Fludarabine and Treosulfan 30 might be of particular value in patients with sAML.…”
Section: Discussionmentioning
confidence: 79%
“…Allogeneic stem cell transplantation (alloSCT) is regarded as the treatment option for sAML with the best chance of achieving a long-term remission. Considering the transplant setting 8,9 , patients with sAML tend to have less available HLA identical siblings, and the majority receive reduced intensity conditioning (RIC) 10,11 . However, it is not clear whether having sAML per se is a risk factor for outcome after alloSCT, when all wellknown risk factors are controlled for 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Data on transplant related factors of importance and outcome specific for s-AML has historically been scarce. However, during 2018-2019 the European Society for Blood and Marrow Transplantation (EBMT), mostly through the work of the Acute Leukemia Working Party, published a series of reports on various aspects of allogeneic transplantation based on large numbers of s-AML patients [149][150][151][152][153][154][155][156]. They show that s-AML, compared to de novo AML, is a risk factor for relapse and survival after HCT [150,154].…”
Section: Allogeneic Stem Cell Transplantationmentioning
confidence: 99%